The potential of cellulose-degrading fungi at various peat maturities in Teluk Bakung Peat Area, Kubu Raya District, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Khotimah S, Suharjono, Ardyati T, Nuraini Y. 2021. The potential of cellulose-degrading fungi at various peat maturities in Teluk Bakung Peat Area, Kubu Raya District, Indonesia. Biodiversitas 22: 1981-1990. Fungi play important roles in degrading cellulose in the maturation process of peat. This study aimed to evaluate the potential of cellulose-degrading fungi at various peat maturities in the forest. Peat soil samples were collected from Teluk Bakung Village, Kubu Raya District, West Kalimantan using a random sampling method. Peat soil samples were obtained at six sampling sites in forests and palm oil plantations. The fungi were cultured by the pour plate method on 1% CMC media. The cellulose-degrading fungi were determined based on a clear zone formation around the colony in CMC agar media. The cellulolytic fungal population in the fibric, hemic, and sapric peats of the secondary forest were 3.2 × 103, 4.6 × 103, and 5.6 × 103 CFU/g, respectively, whereas at fibric, hemic, and sapric of the shrubs were 5.6 x 104, 3.9 × 105 and 4.7 × 104 CFU/g, respectively. Among the 25 cellulolytic fungal isolates, 5 isolates (HS1.5, HS3.4.1, HB2.2, SS2.4.1, and SB2.5.1) showed high average clear zone diameter (21-28 mm). The HS3.4.1 and HS1.5 isolates had cellulase enzyme activity of 132.16 and 127.3 U/mL, respectively. These isolates can grow and degrade cellulose at 30°C to 35°C and pH of 2, 3, 4, and 5.  The HS3.4.1 and HS1.5 isolate were closely related to Penicillium citrinum based on the phylogenetic tree analysis.
Keywords: Peat; fungi; cellulase activity; CMC media; ITS region